Comparison of preparation techniques for CoFeNb/CNTs catalyst - Hamid, H.H. (American Institute of Physics Inc., 2016)
CoFe-based catalysts were prepared using reverse-microemulsion and co-impregnation method. Effect of different preparation techniques on morphology and physiochemical properties of the FTS catalyst CoFeNb/CNTs was investigated. TEM analyses show that the morphological properties of catalysts were affected by preparation techniques. Reverse-micremulsion and co-impregnation method resulted in average particle size of 5.61 nm and 6.20 nm respectively. CoFe-impregnation catalyst is reducible at lower temperature compared to that of reverse-microemulsion catalyst. Acid and thermal treatment of CNTs created defects onto CNTs-support. Â© 2016 Author(s).